Method Of Writing Arabic Letters Follow The Line To Improve The Closeness Between Mothers And Early Children - Asmidar Parapat; Rita Nofianti; Silvia Tri Swara (International Journal of Society and Law, 2024)
Mothers have the responsibility to educate and guide their children in the learning process. Writing the Qur'an is a very important skill for children to have. One of the learning processes that combines learning the Qur'an and children's psychomotor activities in the follow the line method. This study aims to determine how the process of applying the Qur'an writing method in fostering closeness between mothers and children. This study uses a qualitative method with a case study approach. Data were obtained through periodic observation, interviews, and documentation from three pairs of mother and child participants. The research was selected through a purposive sampling method. The criteria for research subjects were six-year-old children who had difficulty writing the Qur'an and lacked closeness with their mothers. The results of this study are: The application of the Qur'an writing method follow the line to increase closeness between mothers and children was successful, closeness with mothers was well established through the learning process of writing the Qur'an follow the line together, children's ability to write the Qur'an has increased and developed. The conclusion is that the Qur'an writing method follow the line can be used to improve the psychological development of mothers and children.